Knowledge, attitudes and behaviour towards ticks and tick-borne diseases—A survey among Lyme borreliosis cases in Bavaria in 2019 - Böhm, Stefanie; Fingerle, Volker; Beyerlein, Andreas; Wildner, Manfred; Böhmer, Merle M. (Ticks and tick-borne diseases, 2025)
•Characteristics derived from LB cases may help identify at-risk groups for targeted prevention.•Participants had knowledge gaps/misconceptions despite experience with ticks/TBDs.•Knowledge and risk perceptions are associated with use of protection measures.•Integrating active/passive TBD education at medical visits could improve prevention. Lyme borreliosis (LB) is the most common tick-borne disease (TBD) in Germany. In Bavaria, the average annual incidence of reported cases was 34.3 cases per 100,000 inhabitants between 2013 and 2020, although case numbers were presumed to be substantially higher. Since no vaccine against LB is currently available, prevention focuses on individual protection measures. This study aims to address knowledge, attitudes, and behaviours among LB cases, a population group at increased exposure to ticks, tick bites and repeated infections. We invited Bavarian LB cases reported between weeks 23 and 35 in 2019 to participate in a questionnaire study. Questions included socio-demographic characteristics, experiences with TBDs, potential tick exposures, details of the recent episode of LB, and knowledge, attitudes, and behaviours regarding TBDs and protection measures. Among the 377 participants, 300 were adults/adolescents, 77 were children (<14 years). Two third resided in rural areas. Although mostly well informed, a significant proportion of participants did not know or were misinformed about availability of repellents (48.5 %), risk of LB in their district (24.9 %), ticks not falling from trees (22.1 %) and non-availability of vaccination against LB (20.9 %). Even though a majority perceived checking for ticks after spending time outdoors, wearing long clothes, wearing closed shoes and tucking pants in socks as effective protection measures against tick bites, a much lower proportion applied those measures frequently (proportions perceived vs. applied: 99.2 % vs. 72.1%; 93.8 % vs. 40.2 %, 88.8 % vs. 51.1 % and 85.4 % vs. 16.8 %, respectively). Identified lack of knowledge or misconception regarding risk factors, availability of protection measures and tick behaviour may hamper application of recommended protection measures. There appeared to be a discrepancy between perceived effectiveness and frequency of application of protection measures. Addressing identified gaps in education campaigns, specifically targeting people living in rural areas, and utilising physician-patient interactions for education are promising entry points to increase awareness and prevent TBDs. Moreover, motivators and barriers for the application of preventive behaviour should be subject of future studies.